Information Intermediaries: How Commercial Bankers Facilitate Strategic Alliances - Frattaroli, Marc; Herpfer, Christoph (Journal of Financial and Quantitative Analysis, 2023)
Abstract We investigate how bankers use information from lending relationships to help borrowers find partners for strategic alliances. Firms that have borrowed from the same banker or share an indirect connection through a network of bankers are significantly more likely to enter an alliance. Consistent with bankers overcoming informational frictions, their ability to facilitate alliances decreases with banker-network distance, and is stronger for opaque borrowers. Firms connected to more potential partners via banker networks enter more alliances. These alliances are associated with positive announcement returns, and brokering banks are more likely to receive future underwriting mandates.